Le nouvel état des fonds du Bundesarchiv de Coblence : réflexions sur l'accès du public aux archives - Ducrot, Ariane (Gazette des archives, 1978)
After the recent publication of the new Guide to the contents of the Bundesarchiv in Koblenz, some reflexions about the policy of Archives for the publicity of their contents : regulations as to access, finding aids, help given to researchers, etc.

Les archives de l'armée allemande - Wolff, Christian (Gazette des archives, 1973)